2020
DOI: 10.1371/journal.pone.0231667
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and scale-up of HIV care and treatment services in four countries over ten years

Abstract: Background Scale-up and expansion of antiretroviral therapy (ART) for people living with HIV (PLHIV) have been a global priority for more than 15 years. Methods We describe PLHIV at enrollment in care and ART initiation in Ethiopia, Kenya, Mozambique and Tanzania from 2005-2014 and report on enrollment location, CD4 count and loss to follow-up (LTF), death, and combined attrition (LTF and death) pre-and post-ART initiation over time. Pre-ART outcomes were estimated using competing risk and post-ART using Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…A limitation of the study is that we can only describe ALHIV enrolled in HIV services who represent only a portion of the population. In addition, loss to follow-up from care is high among adolescents [ 3 , 74 ] and our study was not designed to examine ALHIV who had disengaged from care nor to measure retention or treatment outcomes. While our aim was to describe ALHIV based on mode of transmission, participants were not asked about this directly and information in medical charts was not available.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the study is that we can only describe ALHIV enrolled in HIV services who represent only a portion of the population. In addition, loss to follow-up from care is high among adolescents [ 3 , 74 ] and our study was not designed to examine ALHIV who had disengaged from care nor to measure retention or treatment outcomes. While our aim was to describe ALHIV based on mode of transmission, participants were not asked about this directly and information in medical charts was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies reported on retention in pre‐ART care [ 2 , 20 , 26 , 27 , 34 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], with 12 defining numerators and denominators. Six studies were cross‐sectional and 13 longitudinal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Africa hosts 68% of PLHIV worldwide and in 2018, 62% of AIDS related deaths were from this continent (1). Despite this burden, transformative and remarkable progress has been made in the past decades with regards to the expansion of antiretroviral therapy (ART)(24). In 2018, there were 23 300 000 PLHIV receiving ART, representing 62% of patients in need of treatment.…”
Section: Introductionmentioning
confidence: 99%